Plastic distortion as a fundamental mechanism in nonlinear mesomechanics of plastic deformation and fracture - Panin V. E. Viktor Evgenyevich; Egorushkin V. Е. Valery Efimovich; Panin A. V. Alexey Viktorovich; Chernyavsky A. G. Aleksandr Grigorjevich (2016, 2016)
Title screen